Operating Cost Against Operating Income, Net Interest Margin, Capital Adequacy Ratio and Loan To Deposit Ratio on Profitability - Metyria Imelda Hutabarat; Edy Firmansyah; Achiruddin Siregar (Institute of Computer Science (IOCS), 2022)
Financial performance has become one of the considerations about the condition of banks. The research aims to find out the results of financial ratios effect profitability at state banks in the Indonesia Stock Exchange. The research period is taken for ten years starting from 2012 to 2021. Data collection in this research uses secondary data in the form of data collecting from the annual bank financial statement published on the Indonesia Stock Exchange and by each state-owned bank. The analytical method using multiple linear regression. The results of this research show that Operating Cost against Operating Income (BOPO), Net Interest Margin (NIM), Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR) partially each dependent variable have significant positive effect on profitability (ROA). Simultaneously, BOPO, NIM, CAR and LDR can also have significant positive effect on ROA.